The Effectiveness of Group Acceptance and Commitment Therapy and Cognitive Therapy on Alexithymia and Marital Boredom, Case study: Women Affected by Marital Infidelity in Mashhad, Iran - Maryam Sadeghi; Naeimeh Moheb; Marziyeh Alivandi Vafa (Shahid Sadoughi University of Medical Sciences, 2021)
Introduction: The aim of current paper was to compare the effectiveness of acceptance and commitment group therapy (ACT) and group cognitive therapy (GCT) on Alexithymia and marital boredom (MB) among women affected by marital infidelity in Mashhad. Method: This clinical trial was a double- blind study with a pretest-posttest design in which two intervention groups and one control group were investigated. The study performed on women who realized their spouse infidelity and referred to Azad University Counseling Center in Mashhad in 2018. The sample consisted of 30 women who were selected by purposive sampling and were randomly assigned to two intervention groups and a control group (n=10 per group). The intervention groups were put under ACT training (twelve 90-minute sessions) and GCT training (twelve 90-minute sessions), but the control group did not receive any intervention. Data was obtained by the Toronto Alexithymia Scale-20 and Pines Marital Boredom Scale and was analyzed by multivariate analysis of covariance with SPSS (version 22) software. Results: The results showed a significant reduction in the mean score of MB in the ACT group, also there was a significant reduction in the mean score of Alexithymia in the GCT group (P <0.05). So comparing both therapies, ACT was more influential on reducing marital boredom whereas GCT was more effective on reducing alexithymia. Conclusion: Although both intervention methods were effective on Alexithymia and Marital Boredom in women affected by marital infidelity, it was demonstrated that ACT and GCT have more effect on Marital Boredom and Alexithymia, respectively.